Preliminary Considerations for Analyzing the Legal Framework of Foreign Investments in Peru - Mac Lean, Roberto (1973)
Foreign investments in Peru have been the subject of debate, with arguments ranging from portraying them as a beneficial gift to comparing them to a disguised threat. In this context, this article examines in detail the implications of these investments on the Peruvian economy, recognizing their importance in economic development. It begins by addressing the forms that foreign investment can take: indirect or direct investment, with the latter being a significant source of external capital in Peru. The article then focuses its analysis on the composition of investments and legislation regarding the nationality of companies and investment, exploring criteria for determining their "national" status and the relinquishment of re-exportation of capital and profits as a requirement for the conversion of foreigners to nationals. Additionally, it presents the advantages of these investments such as their contribution to economic growth, but also the disadvantages such as dependency and political influence. Considering this, the author emphasizes the importance of regulating them to maximize benefits and mitigate risks, taking into account the specific reality of the country.